2015
DOI: 10.1007/s11096-015-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional communication training: benefits to practicing pharmacists

Abstract: Pharmacists perceived that a learning and practice module for successful interprofessional practice integrated into a postgraduate clinical pharmacy program enhanced their interprofessional communication skills. The development of pro-active, interprofessional communication skills has the potential to increase interprofessional collaboration and pharmacists' personal role satisfaction. Pharmacists also observed it added value to their professional contribution in health care teams when addressing the demands o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Findings from this study indicated that IPC had many professional related gains. Pharmacists may view IPC as an opportunity to improve their working conditions in the hope of reaching a similar status to their medical colleagues [52], increased professional fulfilment, and an improved professional image [22,25,53]. Collaborations are affected when there is role conflict, ambiguity and hierarchical differences between healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study indicated that IPC had many professional related gains. Pharmacists may view IPC as an opportunity to improve their working conditions in the hope of reaching a similar status to their medical colleagues [52], increased professional fulfilment, and an improved professional image [22,25,53]. Collaborations are affected when there is role conflict, ambiguity and hierarchical differences between healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the above articles focused on an inpatient medical setting 58 . One was based on a postgraduate clinical pharmacy programme at a university setting 60 . The remaining three focused on the collaboration between community pharmacists and general practitioners 52,56,57 .…”
Section: Benefits Of Collaborative Practicementioning
confidence: 99%
“…• interprofessional team process: increased awareness of healthcare professional roles 56,58 , developing trusting interprofessional relationships 58 leading to more collaboration 60 .…”
Section: Benefits Of Collaborative Practicementioning
confidence: 99%
See 2 more Smart Citations